DEVELOPING THE MODEL OF ASSISTANCE, MONITORING AND EVALUATION TO IMPLEMENT LEADER COMMITMENT IN REFUNCTIONING OF HIGHER EDUCATION INTERNAL AUDIT IN MALUKU - Dwi Hariyanti; Jaelani La Masidonda2 (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This paper aims to build a monitoring and evaluation model to implement the leaders and managers commitment of tertiary institutions and government represented by LLDIKTI to increase the role of quality assurance audits. This is a qualitative research with a critical approach. The data is qualitative in primary form that comes from interviews, documentation and secondary data. Research informants are university leaders, managers (foundations) and leaders of LLDIKTI as well as quality assurance implementers. The research results found that all leaders have commitment to active in encouraging the higher education role in quality assurance, monitoring and evaluation model with creating the concept of Logic Model theory. The leaders realize and executing the commitment to encourage the improvement of higher education quality. Therefore, tertiary education institutions in Maluku region have increased the education quality. It was proved by more accreditation for institutions and study programs accredited.